Valuing the public’s demand for crime prevention programs: a discrete choice experiment - Picasso, Emilio (2019)
Fil: Picasso, Emilio. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina